Tracheobronchial Manifestations of Aspergillus Infections - Rafal Krenke; Elzbieta M. Grabczak (The Scientific World Journal)
Human lungs are constantly exposed to a large number of Aspergillus spores which are present in ambient air. These spores are usually harmless to immunocompetent subjects but can produce a symptomatic disease in patients with impaired antifungal defense. In a small percentage of patients, the trachea and bronchi may be the main or even the sole site of Aspergillus infection. The clinical entities that may develop in tracheobronchial location include saprophytic, allergic and invasive diseases. Although this review is focused on invasive Aspergillus tracheobronchial infections, some aspects of allergic and saprophytic tracheobronchial diseases are also discussed in order to present the whole spectrum of tracheobronchial aspergillosis. To be consistent with clinical practice, an approach basing on specific conditions predisposing to invasive Aspergillus tracheobronchial infections is used to present the differences in the clinical course and prognosis of these infections. Thus, invasive or potentially invasive Aspergillus airway diseases are discussed separately in three groups of patients: (1) lung transplant recipients, (2) highly immunocompromised patients with hematologic malignancies and/or patients undergoing hematopoietic stem cell transplantation, and (3) the remaining, less severely immunocompromised patients or even immunocompetent subjects.